Antibiotic Resistances of Yogurt Starter Cultures Streptococcus thermophilus and Lactobacillus bulgaricus - Sozzi, Tommaso (1980)
Twenty-nine strains of Lactobacillus bulgaricus and 15 strains of Streptococcus thermophilus were tested for resistance to 35 antimicrobial agents by using commercially available sensitivity disks. Approximately 35% of the isolates had uncharacteristic resistance patterns.